A Study on Regular Semigroups and its Idempotents - Thomas, Julie; Indhira, K.; M. Chandrasekaran, V. (International Journal of Engineering and Technology, 2018)
An idempotent of a semigroup T is an element e in T such that  In many semigroups, idempotents can be recognized easily. Thus it plays an important role in the structure of semigroups especially on regular semigroups. This article reviews about some research work done about the structure of regular semigroups with a special emphasis on its idempotents.